Determinant Analysis of Motivation and Work Discipline on Employee Achievement (Case Study at PT. Chayani Megajaya Mandiri) - Velline Velline; Yessica Sardina Purba (Jurnal Mantik, 2022)
This study aims to determine the effect of motivation and discipline on employee achievement of PT. Chayani Megajaya Mandiri. This type of research is explanatory research. The Population in this study were all employees of PT. Chayani Megajaya Mandiri, totaling 63 employees. The sampling technique is to use a saturated sample where the entire population will be used as the research sample. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that motivation and discipline partially or simultaneously have a positive and significant effect on employee achievement of PT. Chayani Megajaya Mandiri. Based on the results of this study, the implications for management are to further improve motivation and discipline.